2013
DOI: 10.1371/journal.pone.0064794
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cytotoxic Nanomaterials Enhance Antimicrobial Activities of Cefmetazole against Multidrug-Resistant Neisseria gonorrhoeae

Abstract: The emergence and spread of antibiotic-resistant Neisseria gonorrhoeae has led to difficulties in treating patients, and novel strategies to prevent and treat this infection are urgently needed. Here, we examined 21 different nanomaterials for their potential activity against N. gonorrhoeae (ATCC 49226). Silver nanoparticles (Ag NPs, 120 nm) showed the greatest potency for reducing N. gonorrhoeae colony formation (MIC: 12.5 µg/ml) and possessed the dominant influence on the antibacterial activity with their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Bacterial strains with resistance to an antimicrobial have an advantage both in vitro and in vivo over antimicrobial-susceptible AAAAAGACTTTTT) between the Ϫ10 and Ϫ35 hexamers of the mtrR promoter is shown within the 14 nucleotides in the dotted box, and a T nucleotide that is frequently deleted in strains that overexpress mtrCDE and exhibit a high level of resistance to pump substrates is shown in bold (329). The position of the new Ϫ10 hexamer sequence generated by a point mutation (C to T) that acts as a new promoter (mtr 120 ) for mtrCDE transcription (198) is shown.…”
Section: Antimicrobial Resistance and Gonococcal Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains with resistance to an antimicrobial have an advantage both in vitro and in vivo over antimicrobial-susceptible AAAAAGACTTTTT) between the Ϫ10 and Ϫ35 hexamers of the mtrR promoter is shown within the 14 nucleotides in the dotted box, and a T nucleotide that is frequently deleted in strains that overexpress mtrCDE and exhibit a high level of resistance to pump substrates is shown in bold (329). The position of the new Ϫ10 hexamer sequence generated by a point mutation (C to T) that acts as a new promoter (mtr 120 ) for mtrCDE transcription (198) is shown.…”
Section: Antimicrobial Resistance and Gonococcal Fitnessmentioning
confidence: 99%
“…Notably, several antimicrobials or other compounds, using new targets or mechanisms, were recently developed, and several have shown high in vitro activities against gonococcal isolates. These include novel inhibitors of protein synthesis, e.g., pleuromutilin BC-3781 (318,319) and the boron-containing inhibitor AN3365 (320,321); novel inhibitors of bacterial topoisomerases that target regions different from the fluoroquinolone-binding sites (322,323), such as VT12-008911 (324) and AZD0914 (323,325,326); FabI inhibitors, such as MUT056399 (327,328); noncytotoxic nanomaterials (329); inhibitors of efflux pumps, particularly coadministered with appropriate antimicrobials, that increase the susceptibility to certain antimicrobials, the innate host defense, and toxic metabolites (234,260,330); LpxC inhibitors (331); molecules mimicking host defensins; host defense peptides, such as LL-37 (multifunctional cathelicidin peptide) (332); and IL-12 NanoCap, which is a biodegradable sustained-release formulation of human interleukin 12 that aims to be a therapeutic vaccine against N. gonorrhoeae (TherapyX Inc.). Several of these novel antimicrobials or other types of compounds deserve further attention for their potential use as future treatments for gonorrhea.…”
Section: Future Perspectives For Treatmentmentioning
confidence: 99%
“…9 The application of nanomaterials as delivery vehicles for antibiotics should limit their overmedication in patients, cleaning solutions, bandages, and skin infections. 10 Neurodegenerative disease is an umbrella term for a range of conditions that primarily affect the neurons in the human brain. Examples of neurodegenerative diseases include Parkinson's, Alzheimer's, Huntington's, and Prion diseases.…”
Section: Cancer Imaging and Therapeuticsmentioning
confidence: 99%
“…17,19,20 The enhancement of the efficiency of antimicrobial agents due to their covalent or electrostatic immobilization on the surface of the nanoparticles and cotreatment using nanomaterials containing combinations is a preferable approach in the treatment of bacterial and fungal infections. [21][22][23] The mixed therapy constitutes a method to increase the effectiveness of antibiotic treatment with subsequent reduction in its doses and potential adverse effects. To date, it was demonstrated that silver nanoparticles possess the great potential to be used in the treatment of MDR bacteria, when combined with imipenem, gentamycin, vancomycin (VAN), ciprofloxacin, kanamycin, and chloramphenicol.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Addition of silver nanoparticles enhances as well the antimicrobial and antibiofilm efficiency of ampicillin and VAN against both Gram-positive and Gram-negative bacteria due to increased reactive oxygen species generation. 27 Li et al 21 demonstrated that silver nanoparticles might be employed as an adjuvant compound in combination with cefmetazole against antibiotic-resistant Neisseria gonorrhoeae. However, only few studies have reported that the efficacy of antimicrobial agents can be improved when applied in combination with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%